Using the ideology of geospatial data infrastructure to create a system of accounting and management of land and property complexes of enterprises and local communities, including UTC - Dorosh, Y.; Ibatullin, S.; Tarnopolskyi, Ye.; Tarnopolskyi, A.; Kravchenko, O. (Land Management, Cadastre and Land Monitoring, 2020)
The possibility and expediency of using the ideology of geospatial data infrastructure (hereinafter NIGD) to create a system of accounting and management of land complexes of enterprises and local communities, including UTC, is considered. The need to create accounting systems and management of land and property complexes is due to: large-scale transition to digital technologies in the management of enterprises, institutions and territories, real estate taxation, decentralization processes, the creation of the National Geospatial Data Infrastructure. The necessity to take into account the principles and standards of the national infrastructure of geospatial data is substantiated. Areas have been formed in which information on land and property complexes can be used to fill the National Infrastructure of geospatial data and justify management decisions. Among the key issues that will ensure the use of the ideology of NIGD to create a system of accounting and management of land complexes of enterprises and local communities, including UTC, it is necessary to address the interoperability of data on land complexes, the use of a single cartographic basis, principles and data validation procedures, data error correction, data access mechanisms for process participants, reusability and data licensing.